Carbon Gain Limitation Is the Primary Mechanism for the Elevational Distribution Limit of Myriophyllum in the High-Altitude Plateau - Xie, Dong; Wu, Zhigang; Chen, Han Y. H.; Wang, Zhong; Wang, Qiang; Yu, Dan (Frontiers in Plant Science, 2018)
Temperature comprises a major driver for species distribution and physiological processes in alpine plants. For all terrestrial plant species tested to date, elevation associated decreases in temperature have been observed to influence the balance between carbon acquisition and usage; restricting the upper limit of most alpine trees (i.e., treeline). However, such a carbon source-sink balance has not been tested in any alpine aquatic plants, which is an important component of the alpine aquatic ecosystem. The Myriophyllum species inhabits a broad range of habitats across the high-altitude plateau. Three Myriophyllum species (M. spicatum, M. verticillatum and M. sibiricum) from 12 water bodies at elevational gradients between 2766 m and 5111 m were collected in the Qinghai-Tibetan Plateau. The late growing seasonal concentrations of non-structural carbohydrates (NSC) in the leaves were measured to find how high-altitude conditions influence the carbon balance in aquatic plants. Regression tree analysis separated the 12 water bodies into two groups according to water turbidity (seven water bodies with high turbidity and five water bodies with low turbidity). Overall, leaf NSC concentrations (primarily starch) decreased significantly with increasing elevation in widely distributed M. spicatum and M. verticillatum. Regression tree analysis indicated that water turbidity (i.e., shady environment) was a strong determinant of leaf NSC. In the low turbidity group (< 3.5 NTU), leaf NSC concentrations decreased with increasing elevation; however, in the high turbidity group (> 3.5 NTU), leaf NSC concentrations were low and had no association with elevation. Unlike most recent studies in tree species, which show low temperatures limited growth at high-elevations, our results demonstrated that carbon gain limitation is the primary mechanism for the elevational distribution limit of Myriophyllum species in the Qinghai-Tibetan Plateau. Moreover, water turbidity moderated the effects of low temperature by masking the expected carbon limitation trend. Therefore, at least two environmental factors (i.e., temperature and light availability) induced photosynthesis decreases might explain the NSC responses for aquatic plants in response to elevation.